Fabrication of Organic Solar Cell Utilizing Mixture of Solution-processable Phthalocyanine and Fullerene Derivative with Processing Additive Solvent - Dao, Quang-Duy (VNU Journal of Science: Mathematics - Physics, 2020)
We demonstrate an efficient bulk heterojunction (BHJ) organic solar cell (OSCs) utilizing a soluble phthalocyanine derivative, 1,4,8,11,15,18,22,25-octahexylphthalocyanine (C6PcH 2 ), and a fullerene derivative, 1-(3-methoxy-carbonyl)-propyl-1-1-phenyl-(6,6)C71 and roles of processing additive solvent on improvement of the BHJ OSCs. By adding processing additive solvent, filling factor and short-circuit current density are improved to 0.57 and 8.6 mA/cm 2 , respectively. As a result, the power conversion efficiency of 3.6% is achieved. Otherwise, the effects of processing additive solvent are demonstrated by taking the absorption and photoluminescence spectra of C6PcH 2 and composite thin films into account.